Ciagle po kole : rozmowy z zolnierzami getta warszawskiego - Grupinska, Anka.; Grupinska, Anka. (Warszawa : Wydawn. Ksiazkowe Twoj Styl, 2000)
Personal accounts of soldiers who fought in the Warsaw Ghetto Uprising of 1943.
Continues: Po kole.
Includes index.
Keywords: Jews -- Persecutions -- Poland -- Warsaw; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Personal narratives; Warsaw (Poland) -- History -- Warsaw Ghetto Uprising, 1943 -- Personal narratives